Enhancing Consumer Satisfaction in Coffee Shops Through Service Quality and Strategic Promotions - Tarigan, Miska Irani; Butar-butar, Hana Putri (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The researchers suggest that Kedai Kopi Dolok should work on improving their promotions, such as better messaging about discounts and when they occur, and maintaining high service quality, such as ensuring the place is clean and the staff is friendly. This way, they can continue to satisfy customers! The study's findings demonstrated that providing excellent customer service is essential to ensuring client satisfaction, and promotions are also quite beneficial. In fact, promotions and the quality of the coffee shop's service accounted for 93.2% of customer satisfaction. The remaining 6.8% could be attributed to things like price or the type of products they offer. They used a special computer program called SPSS to understand the answers. The study found a formula that shows how service quality and promotions contribute to customer satisfaction. This shows that service and promotions do indeed satisfy customers, with strong evidence from the trials they conducted. The study examined how good service and promotions at a coffee shop in Tebing Tinggi led to customer satisfaction. To find out, the researchers asked 97 people who visited Kedai Kopi Dolok Ramayana about their feelings about the experience.